The category of life in the light of the theory of events - Asman, Marek (Folia Philosophica, 2005)
The author of the article tries to reveal ideological analogies between the modern conception of the category of life and the principles of the theory of events in Józef Bańka’s theory of recentivism. Ultimately, the author of this article wishes to prove that if we accept the non-casual conceptions of events, which do not require the cause and effect relationship, the idea of life can be explained theoretically. The substantiation of this theory is the goal pursued by the author of this article.